PENGARUH PROGRAM BIMBINGAN PERKAWINAN PRANIKAHAN DAN EFEKTIVITAS TERHADAP CALON PENGANTIN DI KANTOR KEMENTERIAN AGAMA KABUPATEN ASAHAN - Pasaribu, Tetty Salmiah Br (Smart Education, 2025)
Abstract: Premarital marriage guidance program is one of the social service program processes in the form of advisory guidance, assistance given to prospective husband and wife before marriage or called prospective bride and groom (CATIN). In order to obtain welfare and happiness in household life. The purpose of this study was to determine the extent of the influence of the premarital marriage guidance program and its effectiveness both partially and simultaneously on prospective brides and grooms at the Ministry of ReligionofAsahanRegency.The population of this study is the community who have participated in the premarital marriage guidance program during 2023 with a sample of 97 people. This study uses an explanatory research method with a quantitative approach. Based on the results of the analysis using the Pearson correlation product moment statistical test. From Table 4.14, it can be concluded that the premarital marriage guidance program variable (X₁) obtained a T count of 0.903 and based on Table 3.4 it is interpreted to have a very strong influence. Meanwhile, the contribution (direct contribution) of the premarital marriage guidance program variable (X1) to prospective brides and grooms (Y) is of 90.30% while the rest is determined by other variables. While the effectiveness variable (X2) as in Table 4.15 obtained a T count of 0.872 and thus there is a very strong influence. While the contribution of the effectiveness variable (X2) to prospective brides and grooms (Y) is 87.20% and the rest is determined by other variables.The test results of three variables of premarital marriage guidance program (X₁) from the effectiveness (X2) towards prospective brides and grooms (Y) obtained a count of 207.617, so after interpreting the correlation coefficient, the variables of premarital marriage guidance program and effectiveness together are at a very strong level of influence on prospective brides and grooms. While the contribution of variables X₁ and X₂ to Y is 0.940 x 100% = 94.0% and the rest is determined by other variables.Based on the results of the study above, it is recommended to the Office of the Ministry of Religious Affairs of Asahan Regency as follows: 1. Facilities need to be improved, where presentation equipment facilities such as projectors and sound systems are still underused during guidance sessions and participants do not interact enough in discussions and Q&A sessions during premarital marriage guidance sessions. 2. Program monitoring needs to be improved, where the objectives of the premarital marriage guidance program are not clearly explained to all participants at the beginning of the activity and there is a lack of monitoring of the implementation of premarital marriage guidance by involving consultation with facilitators to evaluate the effectiveness of the implementation of premarital marriage guidance. 3. The premarital marriage guidance program at the Office of the Ministry of Religious Affairs of Asahan Regency has a more dominant influence on prospective brides and grooms than effectiveness, so that to improve the quality of prospective brides and grooms by improving the effectiveness of theimplementationprovision Keywords: Premarital Marriage Guidance Program, Effectiveness, Prospective Bride and Groom Abstrak: Program bimbingan perkawinan pranikah merupakan salah salah satu proses program pelayanan sosial yang berupa suatu bimbingan penasehat, pertolongan yang diberikan kepada calon suami isteri sebelum pernikahan atau disebut calon pengantin (CATIN).Agar memperoleh kesejahteraan dan kebahagian dalam kehidupan berumahtangga.Tujuan penelitian ini adalah untuk mengetahui besarnya pengaruh program bimbingan perkawinan pranikah dan efektivitas baik secara parsial dan simultan terhadap calon pengantin di Kementerian Agama Kabupaten Asahan. Populasi penelitian ini adalah masyarakat yang telah mengikuti program bimbingan perkawinan pranikah selama tahun 2023 dengan sampel diperoleh sebanyak 97 orang. Penelitian ini menggunakan metode penelitian penjelasan dengan pendekatan kuantitatif. Berdasarkan hasil analisis menggunakan uji statistik pearson correlation product moment. Dari Tabel 4.14 dapat disimpulkan bahwa variabel program bimbingan perkawinan pranikah (X1) diperoleh rhitung sebesar 0,903 dan berpedoman pada Tabel 3.4 diinterpretasikan berpengaruh sangat kuat. Sedangkan kontribusi (sumbangan langsung) variabel program bimbingan perkawinan pranikah (X1) terhadap calon pengantin (Y) yakni sebesar 90,30 % sedangkan selebihnya ditentukan oleh variabel lain.Sedangkan variabel efektivitas (X2) seperti pada Tabel 4.15 diperoleh rhitung sebesar 0,872 dan demikian terdapat pengaruh sangat kuat. Sedangkan kontribusi variabel efektivitas (X2) terhadap calon pengantin (Y) yakni sebesar 87,20 % dan sisanya ditentukan oleh variabel lain. Hasil pengujian tiga variabel program bimbingan perkawinan pranikah (X1) dan efektivitas (X2) terhadap calon pengantin (Y) diperoleh fhitung sebesar 207,617 maka setelah dilakukan penafsiran terhadap koefisien korelasi maka variabel program bimbingan perkawinan pranikah dan efektivitas secara bersama-sama berada pada tingkat pengaruh sangat kuat terhadap calon pengantin. Sedangkan kontribusi variabel X1 dan X2 terhadap Y yaitu 0,940 x 100 % = 94,0 % dan sisanya ditentukan oleh variabel lain. Berdasarkan hasil penelitian diatas direkomendasikan kepada Kantor Kementerian Agama Kabupaten Asahan sebagai berikut: 1. Perlu diperbaiki sarana, dimana fasilitas alat presentasi seperti proyektor dan sound system masih kurang digunakan selama sesi bimbingan serta peserta kurang berinteraksi dalam diskusi dan tanya jawab selama sesi bimbingan perkawinan pranikah. 2. Perlu diperbaiki pemantauan program, dimana tujuan dari program pelaksanaan bimbingan perkawinan pranikah kurang dijelaskan secara jelas kepada semua peserta pada awal kegiatan dan kurangnya pemantauan pelaksanaan bimbingan perkawinan pranikah dengan melibatkan konsultasi dengan fasilitator untuk mengevaluasi efektivitas pelaksanaan bimbingan perkawinan pranikah. 3. Program bimbingan perkawinan pranikah di Kantor Kementerian Agama Kabupaten Asahan lebih dominan berpengaruh terhadap calon pengantin dibanding efektivitas, sehingga untuk meningkatkan kualitas calon pengantin dengan cara memperbaiki efektivitas pelaksanaan pembekalan. Kata kunci: Program Bimbingan Perkawinan Pranikah, Efektivitas, Calon Pengantin